Inflammasome Activation in Response to the Yersinia Type III Secretion System Requires Hyperinjection of Translocon Proteins YopB and YopD - Zwack, Erin E. (mBio, 2015)
Type III secretion systems (T3SS) translocate effector proteins into target cells in order to disrupt or modulate host cell signaling pathways and establish replicative niches. However, recognition of T3SS activity by cytosolic pattern recognition receptors (PRRs) of the nucleotide-binding domain leucine rich repeat (NLR) family, either through detection of translocated products or membrane disruption, induces assembly of multiprotein complexes known as inflammasomes. Macrophages infected with Yersinia pseudotuberculosis strains lacking all known effectors or lacking the translocation regulator YopK induce rapid activation of both the canonical NLRP3 and noncanonical caspase-11 inflammasomes. While this inflammasome activation requires a functional T3SS, the precise signal that triggers inflammasome activation in response to Yersinia T3SS activity remains unclear. Effectorless strains of Yersinia as well as ΔyopK strains translocate elevated levels of T3SS substrates into infected cells. To dissect the contribution of pore formation and translocation to inflammasome activation, we took advantage of variants of YopD and LcrH that separate these functions of the T3SS. Notably, YopD variants that abrogated translocation but not pore-forming activity failed to induce inflammasome activation. Furthermore, analysis of individual infected cells revealed that inflammasome activation at the single-cell level correlated with translocated levels of YopB and YopD themselves. Intriguingly, LcrH mutants that are fully competent for effector translocation but produce and translocate lower levels of YopB and YopD also fail to trigger inflammasome activation. Our findings therefore suggest that hypertranslocation of YopD and YopB is linked to inflammasome activation in response to the Yersinia T3SS.